Minimal Invasive Surgery for Gastroesophageal Reflux Disease and Hiatus Hernia—Our Experience: A Case Series with Review of Literature - Rafique Umer Harvitkar (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Introduction Laparoscopic fundoplication (LF) has almost completely replaced the open procedure performed for gastroesophageal reflux disease (GERD) and hiatus hernia (HH). Several studies have suggested that long-term results with surgery for GERD are better than a medical line of management. In this retrospective study, we outline our experience with LF over 10 years. Also, we analyze the factors that would help us in better patient selection, thereby positively affecting the outcomes of surgery. Patients and Methods In this retrospective study, we identified 27 patients (14 females and 13 males) operated upon by a single surgeon from 2010 to 2020 at our institution. Out of these, 25 patients (12 females and 13 males) had GERD with type I HH and 2 (both females) had type II HH without GERD. The age range was 24 to 75 years. All patients had undergone oesophago-gastro-duodenoscopy (OGD scopy). A total of 25 patients had various degrees of esophagitis. Two patients had no esophagitis. These patients were analyzed for age, sex, symptoms, preoperative evaluation, exact procedure performed (Nissen’s vs. Toupet’s vs. cruroplasty + gastropexy), morbidity/mortality, and functional outcomes. They were also reviewed to examine the length of stay, length of procedure, complications, and recurrent symptoms on follow-up. Symptoms were assessed objectively with a score for six classical GERD symptoms preoperatively and on follow-up at 1-, 4- and 6-weeks postsurgery. Further evaluation was performed after 6 months and then annually for 2 years. Results 14 females (53%) and 13 males (48%) with a diagnosis of GERD (with type I HH) and type II HH were operated upon. The mean age was 46 years (24–75 years) and the mean body mass index (BMI) was 27 (18–32). The range of duration of the preoperative symptoms was 6 months to 2 years. The average operating time dropped from 130 minutes for the first 12 cases to 90 minutes for the last 15 cases. The mean hospital stay was 3 days (range: 2–4 days). In the immediate postoperative period, 72% (n = 18) of the patients reported improvement in the GERD symptoms, while 2 (8%) patients described heartburn (grade I, mild, daily) and 1 (4%) patient described bloating (grade I, daily). A total of 5 patients (20%) reported mild dysphagia to solids in the first 2 postoperative weeks. These symptoms settled down after 2 to 5 weeks of postoperative proton-pump inhibitor (PPI) therapy and by adjusting consistency of oral feeds. There was no conversion to open, and we observed no perioperative mortality. There were no patients who underwent redo surgeries in the series. Conclusion LF is a safe and highly effective procedure for a patient with symptoms of GERD, and it gives long-term relief from the symptoms. Stringent selection criteria are necessary to optimize the results of surgery. Experience is associated with a significant reduction of operating time.